Brain cancer cluster investigation around a factory emitting dichloromethane - Makris, Konstantinos C.; Voniatis, Michael (My University, 2018)
Background: The health risks associated with dichloromethane (DCM) for the general population living near industrial activities have not yet been quantified, primarily due to lack of epidemiological datasets. In the absence of such human data, we undertook a cancer cluster investigation in Cyprus around a historically using DCM plant producing shoe soles that were globally exported. We designed the methodology to investigate the possible existence of a cancer cluster in the area around the factory (point zero) and within a radius of 500 meters. Methods: A retrospective comparative population study was designed using a group of cancer patients living or working in the chosen geographical area around the factory. Results: Mean stack emissions of DCM of 88 mg/Nm(3) and flow rates of 850 g/h exceeded the permissible DCM limits established for industrial zones. Brain and central nervous system (CNS) cancer incidence rates showed significant (P < 0.001) increase in the study area around the plant when compared with those observed in other areas of Cyprus. Calculated standardized incidence ratios for brain/CNS after adjusting for the age at diagnosis ranged from 11.3-25.7 [mean 6.5 (3.02 : 12.3)] for the study area. Conclusions: We showed the association between chronic, unintentional DCM exposures and brain/CNS cancer cases for the general population located in a residential area being in close proximity with a plant historically emitting DCM.
Keywords: Brain tumors; Cancer; Central nervous system; Central nervous system neoplasms; Exposure; Cyprus; Geographic area; Methylene chloride; Plants; Radius; Shoes; Brain diagnosis; Fluid flow; Datasets